Membangun dan Mengimplementasikan Budaya Inovatif di Organisasi Modern: Analisis Strategi dan Praktik Terbaik untuk Meningkatkan Daya Saing Organisasi Publik - Putri, Bella Kharisma; Frinaldi, Aldri (Al-DYAS, 2024)
The aim of writing this article is to look at corruption in the form of abuse of official authority in Indonesia. This article applies a qualitative method by applying a descriptive analysis system in presenting it. The data collection technique for this research is a library research library study sourced from various reading literature and previous research articles regarding corruption, a form of abuse of official authority in Indonesia. The rise in public officials caught in corruption cases is no longer a surprising phenomenon. Apart from allegations of self-enrichment, receiving gratuities and bribes, the status of corruption suspects is also given to those who, because of their policies, are suspected of causing state losses.